Internationalization: Unintended Consequences? - Knight, Jane (International Higher Education, 2009)
International Student Populations have risen dramatically in Australian tertiary education, allowing a drop in the amount required to publicly fund education; however, concerns arise that reliance on international student tuition may adversely effect quality, and a focus on education as industry (and it is currently Australia's 3rd largest export) may skew educational priorities.